Konseling Lintas Budaya dalam Mengatasi Kesalahpahaman Komunikasi Mahasiswa Berbudaya Batak di Lingkungan Multikultural - Laila Sari; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the application of cross-cultural counseling in overcoming communication misunderstandings in Batak cultured students in a multicultural environment. Problems arise due to differences in communication culture between the counselee and their social environment. This study used a single subject experimental method or Single Subject Research (SSR) with a baseline phase design 1 (A1), treatment (B), and baseline 2 (A2). The subject was a student with the initials MR, aged 20 years, who experienced communication barriers due to cultural differences. Data collection techniques were carried out through observation, interviews, and behavioral assessment sheets. The intervention provided was cross-cultural counseling services using assertiveness, empathy, reflection, and role-playing techniques. Data analysis was carried out descriptively qualitatively by comparing the condition of the counselee before and after the intervention. The results of the study showed that cross-cultural counseling was able to help the counselee understand differences in communication culture in a more positive and adaptive manner. After being provided with counseling services, the counselee began to be able to control the volume of voice and intonation when speaking, increase self-confidence, reduce social anxiety, and rebuild better social relationships with their surroundings. Cross-cultural counseling also helps clients understand that communication adjustments do not mean eliminating their original cultural identity, but rather a form of adaptation in a multicultural environment. Thus, cross-cultural counseling plays a crucial role in helping students overcome communication barriers caused by cultural differences and create harmonious social relationships.